Alteration in cellular viability, pro-inflammatory cytokines and nitric oxide production in nephrotoxicity generation by Amphotericin B: Involvement of PKA pathway signaling - França, F. D.; Ferreira, A. F.; Lara, R. C.; Rossoni, J. V.; Costa, D. C.; Moraes, K. C M; Tagliati, C. A.; Chaves, M. M. (Wiley, 2013)
Amphotericin B is one of the most effective antifungal agents; however, its use is often limited owing to adverse effects, especially nephrotoxicity. The purpose of this study was to evaluate the effect of inhibiting the PKA signaling pathway in nephrotoxicity using Amphotericin B from the assessment of cell viability, pro-inflammatory cytokines and nitric oxide (NO) production in LLC-PK1 and MDCK cell lines. Amphotericin B proved to be cytotoxic for both cell lines, as assessed by the mitochondrial enzyme activity (MTT) assay; caused DNA fragmentation, determined by flow cytometry using the propidium iodide (PI) dye; and activated the PKA pathway (western blot assay). In MDCK cells, the inhibition of the PKA signaling pathway (using the H89 inhibitor) caused a significant reduction in DNA fragmentation. In both cells lines the production of interleukin-6 (IL)-6 proved to be a dependent PKA pathway, whereas tumor necrosis factor-alpha (TNF-α) was not influenced by the inhibition of the PKA pathway. The NO production was increased when cells were pre-incubated with H89 followed by Amphotericin B, and this production produced a dependent PKA pathway in LLC-PK1 and MDCK cells lines. Therefore, considering the present study's results as a whole, it can be concluded that the inhibition of the PKA signaling pathway can aid in reducing the degree of nephrotoxicity caused by Amphotericin B. © 2013 John Wiley & Sons, Ltd.
Keywords: Amphotericin B; IL-6; LLC-PK1; MDCK; Nephrotoxicity; NO; PKA; TNF-α